2017
DOI: 10.3389/fnmol.2017.00114
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Protocadherins Are Required for Building Functional Neural Circuits

Abstract: Neuronal identity is generated by the cell-surface expression of clustered protocadherin (Pcdh) isoforms. In mice, 58 isoforms from three gene clusters, Pcdhα, Pcdhβ, and Pcdhγ, are differentially expressed in neurons. Since cis-heteromeric Pcdh oligomers on the cell surface interact homophilically with that in other neurons in trans, it has been thought that the Pcdh isoform repertoire determines the binding specificity of synapses. We previously described the cooperative functions of isoforms from all three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
3
30
1
Order By: Relevance
“…week (Duan et al, 2019;Minlebaev et al, 2011;Pangratz-Fuehrer and Hestrin, 2011). cPcdh deletions result in abnormal network activities in spinal cord and synchronized activities in vitro (Hasegawa et al, 2017)…”
Section: Pcdhg-dependent Interactions and Cin Survivalmentioning
confidence: 99%
“…week (Duan et al, 2019;Minlebaev et al, 2011;Pangratz-Fuehrer and Hestrin, 2011). cPcdh deletions result in abnormal network activities in spinal cord and synchronized activities in vitro (Hasegawa et al, 2017)…”
Section: Pcdhg-dependent Interactions and Cin Survivalmentioning
confidence: 99%
“…These observations are consistent with functions revealed by analyses of Pcdha or Pcdhg mutant mice, which indicated that α- and γ-Pcdhs play critical roles in neuronal survival, axon and dendrite arborization, self-avoidance, and tiling, and synaptogenesis, depending on the neuronal subtype examined [109, 137, 140152]. Comparison of mice lacking all three Pcdh gene clusters with those lacking only the Pcdha, Pcdhb , or Pcdhg clusters indicates overlapping and synergistic functions for the clustered Pcdh families, though the most severe phenotypes are generally attributable to loss of the γ-Pcdhs [153, 154]. Individual non-clustered δ-Pcdhs are expressed by discrete neuronal subsets throughout the brain, and functional studies collectively have revealed roles in axon outgrowth and pathfinding, synaptic plasticity, and synapse elimination [84, 86, 110, 155163].…”
Section: Protocadherinsmentioning
confidence: 99%
“…In mouse, the Pcdha cluster encodes 14 α-Pcdhs, the Pcdhb cluster encodes 22 β-Pcdhs, and the Pcdhg cluster encodes 22 γ-Pcdhs ( Fig 1A). While all three Pcdh gene clusters contribute to neural development to some extent [4][5][6][7][8][9][10], the Pcdhg locus is the only one required for postnatal viability, and disruption of this locus results in the strongest phenotypes (reviewed in [11]).…”
Section: Introductionmentioning
confidence: 99%